2006
DOI: 10.1002/gps.1686
|View full text |Cite
|
Sign up to set email alerts
|

The effect of perceived forgetfulness on quality of life in older adults; a qualitative review

Abstract: SUMMARYBackground Approximately 50% of older individuals perceive themselves as being forgetful. Objective The objective of this review is to get an overview of previous research on the relation between perceived forgetfulness (in the absence of objective memory deficit) and quality of life in older individuals. Findings in previous research might be a starting point for further research and possible future interventions. Methods Scientific papers that investigated the relation between subjective memory compla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
87
1
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 26 publications
5
87
1
7
Order By: Relevance
“…Nevertheless, recent studies have shown that negative metamemory can reduce engagement in cognitive and social activities (Valentijn et al, 2006), whose effects are thought to have a positive impact on cognitive ageing (Hultsch et al, 1999;Kramer and Willis, 2002;Kliegel et al, 2004). Moreover, negative perceptions of one's own memory could reduce well-being (Mol et al, 2007). Our results show that metamemory may vary with aging, depressive symptoms and routinization.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Nevertheless, recent studies have shown that negative metamemory can reduce engagement in cognitive and social activities (Valentijn et al, 2006), whose effects are thought to have a positive impact on cognitive ageing (Hultsch et al, 1999;Kramer and Willis, 2002;Kliegel et al, 2004). Moreover, negative perceptions of one's own memory could reduce well-being (Mol et al, 2007). Our results show that metamemory may vary with aging, depressive symptoms and routinization.…”
Section: Discussionmentioning
confidence: 53%
“…This result showed the importance of memory self-efficacy in memory functioning for elderly people, and that this could influence the motivation and confidence to engage in novel activities (Lachman et al, 1987). Consequently, metamemory could have impact on the objective and subjective quality of life (Mol et al, 2007), and various authors have claimed the importance of metamemory in the capacity to fit with environment changes and integrate memory modifications during aging (e.g., Bieman-Copland and Charness, 1994).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…It is thus clear that a common complaint of normally aging individuals refers to cognitive changes. The presence of such perceived cognitive losses significantly contributes to a lowered quality of life (Mol et al, 2007;Mol, van Boxtel, Willems, Verhey, & Jolles, 2009). These cognitive problems are a source of worry and frustration for many aging individuals.…”
Section: Introductionmentioning
confidence: 99%